Effects of hurricane-driven deforestation and reforestation on diurnal soil temperature changes in the Tatra Mountains in southern Poland - Joanna Paulina Siwek (Acta Scientiarum Polonorum. Formatio Circumiectus, 2021)
Aim of the study: The aim of the study was to investigate the effect of hurricane-driven deforestation and reforestation on diurnal changes in soil temperatures in the Tatra Mountains (Poland).